Enhancing peppermint growth: Investigating the interplay of Biochar and Nitrogen levels - Hasan Haghighatnia; Ebrahim Talebi; Maryam Khosravi Nezhad (Universitas Sebelas Maret, 2024)
Peppermint (Mentha piperita) is valued for its medicinal properties and applications in the food and health industries. However, optimizing growth conditions to enhance yield and quality remains challenging. The study aimed to evaluate the impact of nitrogen and biochar on peppermint growth, elemental content, and biochemical composition, using a factorial experiment with a randomized block design and four-pot replications during the 2022-2023 crop year. Biochar levels up to 2% by weight increased plant height by 25%, chlorophyll index by 20%, leaf count by 18%, and dry weights of shoots and roots by 15%, but declined beyond this threshold. Nitrogen levels up to 75 mg per gram of soil increased plant height by 33.8%, chlorophyll index by 30%, and dry weights of aerial organs by 28%. Elemental concentrations in aerial organs peaked at 3% biochar, increasing potassium by 22%, phosphorus by 18%, and calcium by 15%, while zinc and copper decreased by 10% and 12%, respectively. Anthocyanin, flavonoid, and total phenol concentrations decreased by 20%, 30%, and 35% respectively with increasing biochar and nitrogen levels. Applying up to 2% biochar by weight optimizes peppermint yield. Nitrogen mitigates adverse effects of high biochar levels, with 50 mg nitrogen recommended at 2% biochar for optimal yield. These findings offer sustainable agricultural practices to improve crop productivity in nutrient-deficient soils and promote environmentally friendly agricultural practices.